1994
DOI: 10.1056/nejm199406303302601
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporine in Severe Ulcerative Colitis Refractory to Steroid Therapy

Abstract: Intravenous cyclosporine therapy is rapidly effective for patients with severe corticosteroid-resistant ulcerative colitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
993
4
50

Year Published

1997
1997
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,559 publications
(1,084 citation statements)
references
References 15 publications
17
993
4
50
Order By: Relevance
“…18 The fact that calcineurin inhibitors, which mainly suppress the expression of IL2, are effective in treatment-resistant UC, but not in CD, might also point to a key role for this interleukin in UC. 28 Further support for the importance of IL2 in UC comes from the fact that a pilot trial with antibodies against the IL2 receptor in treatment-resistant UC was successful. 29 The fact that both a lack of IL2 and an excess of IL2 predispose to colitis is however puzzling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 The fact that calcineurin inhibitors, which mainly suppress the expression of IL2, are effective in treatment-resistant UC, but not in CD, might also point to a key role for this interleukin in UC. 28 Further support for the importance of IL2 in UC comes from the fact that a pilot trial with antibodies against the IL2 receptor in treatment-resistant UC was successful. 29 The fact that both a lack of IL2 and an excess of IL2 predispose to colitis is however puzzling.…”
Section: Discussionmentioning
confidence: 99%
“…Allelic association testing and a pooled analysis using a Cochran-Mantel-Haenszel test were performed. Results: All four SNPs were strongly associated with UC in all three cohorts and reached genome-wide significance in the pooled analysis (rs13151961 p = 1.35610 210 , rs13119723 p = 8.60610 28 , rs6840978 p = 3.07610 28 , rs6822844 p = 2.77610 29 ). A moderate association with CD was also found in the pooled analysis (p value range 0.0016-9.86610 25 ).…”
mentioning
confidence: 94%
“…Clinical disease activity was determined by the Colitis Activity Index (CAI) [24] (from 0 to 21; severe disease defined as > 12, inactive disease < 4) on week 0 or just before treatment, and after 1, 2, 4, 6 and 8 weeks of treatment. Quality of life was assessed at week 1, 4 and 8 by means of the Inflammatory Bowel Disease Questionnaire (IBDQ) [25].…”
Section: Methodsmentioning
confidence: 99%
“…Treatment was discontinued if there was no improvement after 4 weeks according to the CAI [24], or in any patient with progression of disease activity at any control visit. Other predefined reasons for discontinuation were heparin-induced thrombocytopenia (HIT) type 2 [27,28] and/or severe bleeding (defined as Hb < 5.0 mmol/l, Hb > 2.0 mmol/l below baseline value, blood loss with blood pressure <80/50 mmHg and/or need for blood transfusion).…”
Section: Methodsmentioning
confidence: 99%
“…20,21 A multicentre double-blind, randomized, controlled trial in North America demonstrated the bene®t of intravenous cyclosporin for severe ulcerative colitis refractory to intensive steroid therapy compared to placebo. 22 Twenty patients were randomized to receive either cyclosporin or placebo after 7±10 days of unsuccessful steroid therapy. Nine of 11 patients who received cyclosporin (i.e.…”
Section: Response To Treatmentmentioning
confidence: 99%